Evaluation of Ecotourism Resources: A Case Study of Nameri National Park of Assam (India) - Das, Niranjan; Deori, Sujata (Revista Brasileira de Ecoturismo (RBEcotur), 2012)
Tourism is currently the world’s largest industry (US$ 3.4 trillion annually) and ecotourism represents the fastest growing sector of this market. The term ‘Ecotourism’ was first coined by “Hector Ceballos Lascurain” in 1983, and was initially used to describe nature-based travel to relatively undisturbed area with an emphasis on education. Assam, comprising Eastern Himalaya is one of the Mega bio-diversity hot spots of the world (MYERS, 1991). It also forms part of two endemic bird areas, viz Eastern Himalaya and Assam plains (COLLAR et al., 1994). Nameri National Park is a part of NBL (North Bank Landscape) and also is a part of Eastern Himalayan Mega Biodiversity Hotspot has immense potentialities for the ecotourism venture. The present research can provide an assessment of potential sites within the park, which can speed up tourism infrastructural development. Through the paper the author tries to highlight such possibilities on the basis of assessment of potentials Ecotourism resources of the Nameri National Park through field experience gained different parts of the study area.